Trends in Antarctic Ice Sheet Elevation and Mass. Issue 14 (24th July 2019) - Shepherd, Andrew; Gilbert, Lin; Muir, Alan S.; Konrad, Hannes; McMillan, Malcolm; Slater, Thomas; Briggs, Kate H.; Sundal, Aud V.; Hogg, Anna E.; Engdahl, Marcus E.
Abstract: Fluctuations in Antarctic Ice Sheet elevation and mass occur over a variety of time scales, owing to changes in snowfall and ice flow. Here we disentangle these signals by combining 25 years of satellite radar altimeter observations and a regional climate model. From these measurements, patterns of change that are strongly associated with glaciological events emerge. While the majority of the ice sheet has remained stable, 24% of West Antarctica is now in a state of dynamical imbalance. Thinning of the Pine Island and Thwaites glacier basins reaches 122 m in places, and their rates of ice loss are now five times greater than at the start of our survey. By partitioning elevation changes into areas of snow and ice variability, we estimate that East and West Antarctica have contributed −1.1 ± 0.4 and +5.7 ± 0.8 mm to global sea level between 1992 and 2017. Plain Language Summary: Climate change can trigger long‐term loss in ice sheet mass, which in turn drives global sea level rise. To isolate this signal, short‐term fluctuations in snowfall have to be accounted for in measurements of ice sheet elevation change. In this study, we do this by combining satellite altimetry and a regional climate model. This allows us to show that the extent of ice sheet dynamical imbalance has grown over the past 25 years to incorporate 24% of the West Antarctic Ice Sheet. The thinning of Antarctic glaciers reaches 122 m in places, and their combined ice losses have increased by a factor of 5. Altogether, Antarctica has contributed 4.6 ± 1.2 mm to global sea level rise. Key Points: We combine satellite radar altimetry and a regional climate model to separate changes in Antarctic elevation into snow and ice contributions Between 1992 and 2017, ice thinning has grown in extent to include 24% of West Antarctica and reaches 122 m in places Ice losses from Pine Island and Thwaites Glaciers have risen fivefold; East and West Antarctica have contributed 4.6 ± 1.2 mm to sea level